2020
DOI: 10.3201/eid2610.201702
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Social Distancing Measures on Coronavirus Disease Healthcare Demand, Central Texas, USA

Abstract: Social distancing orders have been enacted worldwide to slow the coronavirus disease (COVID-19) pandemic, reduce strain on healthcare systems, and prevent deaths. To estimate the impact of the timing and intensity of such measures, we built a mathematical model of COVID-19 transmission that incorporates age-stratified risks and contact patterns and projects numbers of hospitalizations, patients in intensive care units, ventilator needs, and deaths within US cities. Focusing on the Austin metropolitan area of T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 26 publications
(29 reference statements)
4
93
0
Order By: Relevance
“…This agrees with Wang et al [18] who use a stochastic age-and risk-structured susceptible-exposed-asymptomaticsymptomatic-hospitalized-recovered (SEAYHR) model to considered the effect of various levels of social distancing.…”
Section: Discussionsupporting
confidence: 89%
“…This agrees with Wang et al [18] who use a stochastic age-and risk-structured susceptible-exposed-asymptomaticsymptomatic-hospitalized-recovered (SEAYHR) model to considered the effect of various levels of social distancing.…”
Section: Discussionsupporting
confidence: 89%
“…We find that magnitude of the reductions in average mobility, and the resulting increases in residential mobility, are important in determining the size of reduction in R t . This agrees with Wang et al 19 who use a stochastic age-and risk-structured susceptible-exposed-asymptomatic-symptomatic-hospitalised-recovered (SEAYHR) model to considered the effect of various levels of social distancing. They found that social distancing measures, which reduced nonhousehold contacts by <50%, would not prevent a healthcare crisis and that only their 75% and 90% contact reduction scenarios were projected to enable metropolitan areas to remain within healthcare levels.…”
Section: Discussionsupporting
confidence: 89%
“…We would also like to thank David Joerg and Jacob Steinhardt for their comments through Open Review. This research was partly funded by the Imperial College COVID- 19…”
Section: Acknowledgementsmentioning
confidence: 99%
“…By implementing this prevention and protection measure endorsed in a place of work, it will potentially improve to defeat this COVID-19 pandemic [38]. Governments must consequently rapidly take accurate and inclusive measures to prevent the spread of the epidemic [39].…”
Section: Prevention Measures and Covid-19mentioning
confidence: 99%